FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA LEMBAGA PERKREDITAN DESA - Buda Utama, I Dewa Gede; Sadha Suardikha, I Made (E-Jurnal Akuntansi, 2014)
This study aims to determine the factors that affect the performance of accounting information systems. The location of research at Village Credit Institutions in  Sukasada District. Purposive sampling technique is used to obtain the sample amounted to 63 peoples. Multiple linear regression analysis technique used in this study. This study funds that the user involvement, the ability of the technique of personal, organizational size, top management support, the presence of prominent representatives had no effect on user satisfaction. Formalization of system development as well as education and training programs affect user satisfaction. The users involvement and the formalization of system development affects the use of the system. Engineering capabilities of personal, organizational size, top management support, as well as the presence of prominent representatives of education and training programs do not affect the use of the system.
Keywords: accounting information system performance